Виртуальные информационные студенческие сообщества и компьютерные сети кампусов - Ткачев, В. Н. (ХНУРЕ, 2011)
The ways of development student informative society are considered in these theses. Problems are selected and the ways of overcoming are offered.
Keywords: компьютерная сеть; виртуальное сообщество; общежития ХНУРЭ